Identifikasi Kelengkapan Informasi Dan Keakuratan Kode Dokumen Rekam Medis Terkait Penentuan Tarif Biaya Pasien Bpjs Di Rsud Pandan Arang Boyolali - SAPUTRI, RIZKI ORYZA FEBTIAYU NUR; , Sri Sugiarsi, SKM, M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Rizki Oryza Febtiayu Nur Saputri. J410 131 036 Identification In Comprehensiveness Of Information And The Accuracy Code Medical Record Document Related To The Determination Patients BPJS Cost In RSUD Pandan Arang Boyolali ABSTRACT The completeness of charging administrative data and data medical patient bpjs at RSUD Pandan Arang Boyolali still find any incompleteness on a medical record documentin-patient. This will influence on the claims financing of BPJS. The aim of this research is a analyze comprehensiveness of information and the accuracy code on a document record medical inpatients in the tariff determination patients the cost of BPJS. The kind of research using mixed methodology with the cross sectional. The population in this research was a beam medical record in-patient cases of a disease in the fourth quarter.Technique of sampling using purposive sampling and samples as much as 121. The result of research shows that the percentage charging information administration medical record document of administrative aspects and medical aspects range 62.5% -78% (<100%) so that concluded incomplete. The percentage accuracy diagnosis code complete 100% only diagnosis hypertensive, while other diseases ranged from 30-90%. The percentage accuracy the act code of highest only 20% for diagnosis diabetes mellitus and chronic kidney disease, while others range 0-10% .The implementation of charging informationand implementation of the encoding by officers had worked obey standars operating procedures but not yet go entirely according to expected. Keywords : Information Completeness, The Accuracy Code, The Determination of Tariff.